Haoles in Hawaiʻi - Rohrer, Judy (Race and ethnicity in Hawaiʻi., 2010)
Examines the the historical and contemporary place of haoles (white people) in Hawaii, recognizing this as a form of American whiteness specific to Hawaii, and arguing that "haole" was forged and reforged over two centuries of colonization and needs to be understood in that context.